Using nanoBRET and CRISPR/Cas9 to monitor proximity to a genome-edited protein in real-time - Carl W. White; Hannah K. Vanyai; Heng B. See; Elizabeth K. M. Johnstone; Kevin D. G. Pfleger (Scientific Reports, 2017)
Abstract Bioluminescence resonance energy transfer (BRET) has been a vital tool for understanding G protein-coupled receptor (GPCR) function. It has been used to investigate GPCR-protein and/or -ligand interactions as well as GPCR oligomerisation. However the utility of BRET is limited by the requirement that the fusion proteins, and in particular the donor, need to be exogenously expressed. To address this, we have used CRISPR/Cas9-mediated homology-directed repair to generate protein-Nanoluciferase (Nluc) fusions under endogenous promotion, thus allowing investigation of proximity between the genome-edited protein and an exogenously expressed protein by BRET. Here we report BRET monitoring of GPCR-mediated β-arrestin2 recruitment and internalisation where the donor luciferase was under endogenous promotion, in live cells and in real time. We have investigated the utility of CRISPR/Cas9 genome editing to create genome-edited fusion proteins that can be used as BRET donors and propose that this strategy can be used to overcome the need for exogenous donor expression.